(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study aims to determine how brand awareness, perceived quality, brand association, and brand loyalty affect brand equity of Apple products (Case Study of Students of the Faculty of Economics, Sanata Dharma University). The method used in this research is a quantitative method that is a confirmatory and exploratory research method. The population in this study involved 168 respondents from the Faculty of Economics, Sanata Dharma University from the class of 2020-2023 who had used Apple products for at least two products, the sampling method for this study was taken using purposive sampling technique. The research data were obtained from the results of a survey distributed through a questionnaire to respondents online. Then the data that has been collected is tested using data analysis techniques such as normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, simultaneous test (F test) and partial test (T test). The results of this study state that brand awareness and brand association of Apple products have a positive and significant effect on Apple product brand equity, while perceptions of quality and Apple brand loyalty have no positive and significant effect on Apple product brand equity.